Decision Support System in Determining Lecturer Performance with the TOPSIS Method - Sefrika, S (IJISTECH (International Journal of Information System and Technology), 2023)
In order to improve the quality of learning in tertiary institutions, it is necessary to carry out periodic evaluations so that the quality of education can increase and adapt to needs. Performance appraisal is carried out in order to know the teaching and interpersonal quality of the lecturers so that they are in line with the education quality standards. To determine the best lecturer performance, it needs to be done further in order to get accurate results. This study aims to determine the best lecturer performance by using the TOPSIS method decision support system. TOPSIS is a method that can solve multi-criteria problems so as to get maximum results. The results show that the most ideal criterion in determining outstanding lecturers is the pedagodic aspect. Research can be used in multi-criteria decision-making processes with accurate results.